Renewable Assignments in Open Pedagogy in Mathematics - Sebastian, Vini (SXC Journal, 2026)
Open Pedagogy engages students not just as passive recipients of knowledge rather creators of knowledge. Students in open pedagogy learn to adapt knowledge or create new knowledge and develop open educational resources that can be used by other learners. Assignments are used by many institutions as a technique of testing students on higher order learning. In Higher educational institutions, these assignments have a onetime value for evaluation and awarding grades. Renewable Assignments in Open pedagogy is a resource rather than a product that is used just for evaluation and grading. In Mathematics it is very significant to engage pupils in renewable assignments, as pupils can have a snowballing learning experience. Many institutions accept physical assignments and collect it for physical inspections and marking. These assignments of students have embedded creativity which would be a waste if not used effectively. Therefore, to make assignments sustainable, teachers must design good assignments and enable pupils to develop useful skills. This requires change in attitude and positive action. Students’ attitude towards assignment and evaluation must change if we need this continuous fl ow of creativity in the teaching learning process. The paper emphasizes recycling of assignments for optimal use. The paper also mentions techniques of teaching which can make students as knowledge creators rather than recipients of knowledge. The paper advocates non disposable/renewable assignments for sustainability in evaluation.